Impact of corporate governance reforms on financial reporting quality in selected Middle Eastern Countries - Husseinali, Ahmed (2015)
Financial crises that affected the stock markets in the Middle Eastern countries highlighted the importance of the financial reporting quality and the needs for financial reforms that can develop financial reporting system. Studies on financial reporting quality (FRQ) have been neglected in the Middle East region. Although in recent years many Middle Eastern countries have initiated western-style corporate governance (CG), little research has been attempted to assess the impact of improved CG reform on FRQ. The present study addresses these shortcomings by setting three objectives using a sample of non-financial firms listed on the Saudi Stock Exchange (Tadawul), the Abu Dhabi securities exchange (ADX), representing the United Arab Emirates (UAE), and the Qatar stock exchange (QSE). The study employed five characteristics of the companies’ board of directors as measures; namely, Chief Executive Officer (CEO) duality, presence of independent members of the board of directors, holding of multiple directorships, financial expertise of directors, and social title of directors, as well as two ownership characteristics; namely, directors’ ownership and institutional ownership. The first objective of this study is to investigate the impact of CG reform on FRQ. This which achieved by investigating the trends of FRQ before and after the introduction of CG reform, where an independent sample t-test was used to examine the differences between firms’ FRQ averages before and after the reform was introduced. The second objective is to investigate the effect of changes required in the composition of boards of directors and ownership structures on FRQ, using a regression model under fixed effects estimators. In order to measure the FRQ, the study adopted Working Capital Accruals quality (WCAQ) as the most appropriate measure to capture the transparency and reliability of the financial reporting. The third objective is to assess the moderation role of CG reform on the relationship between CG characteristics and FRQ, which was achieved through including interaction terms for the CG reform and the variables of interest. The main findings of this study indicate that reform in CG was indeed associated with an improvement in FRQ in both Saudi Arabia and the United Arab Emirates (UAE), but not in the Qatar sample. The result of test for the second objective indicated that characteristics of Saudi boards of directors and ownership structure can explain the variation of firms FRQ to a greater extent than those of UAE and Qatar governance principles. The study contributes to the theory by extending financial reporting quality and corporate governance reform in accounting. The implications of this study include; government regulators can use the findings of this study to evaluate CG frameworks in their respective countries; and policymakers, can gain a better understanding of the weaknesses and the strengths of recent CG reform in their countries. The findings suggested that Middle Eastern countries should develop their CG system based on the real needs of the local stock market in order to enhance their financial reporting systems.